The mediating effect of group identity and religious fundamentalism on the association of intergroup contact with prejudice - Sulistio, Sulistio; Suryanto, Suryanto; Hadziq, Abdullah; Bulut, Sefa (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2020)
Contact between groups continues to be recognized as a variable that affects prejudice. The effectiveness of the impact of such contacts on prejudice is influenced by other variables, according to the characteristics of the group. This study aims to determine the effect of group identity mediation and religious fundamentalism on the influence of intergroup contact on the prejudice of transnational Islamic groups against moderate Islamic ones. The research subjects were selected randomly from 365 members of Jama’ah Tabligh, a transnational Islamic group in Semarang, Indonesia. The research data collection used the scales of prejudice, intergroup contact, group identity, and religious fundamentalism, while the data analysis employed structural equation modeling (SEM). The results show that group identity and religious fundamentalism have a mediating effect on intergroup contact's impact on the prejudice of transnational Islamic groups against moderate ones. This research's theoretical implication is that the extent of the influence of intergroup contacts on prejudice is affected by group identity and religious fundamentalism as mediating variables.